Pluralisme Sosial Keagamaan Menuju Karakter Bangsa Yang Shalih - Zahratunnisa Hamdi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
The questioning argued that the social problems of the community were directed at the 2005 MUI fatwa which prohibits pluralism. MUI is seen as wrongly assessing the addition of the word